MODEL PENGEMBANGAN ENTERPRENEURSHIP DALAM PEMBERDAYAAN EKONOMI RUMAH TANGGA PADA MASYARAKAT MATRILIENAL MINANGKABAU (Jurnal Pelangi : Research of Education and Development, 2013)
The main focus of this research is to investigate and understand the women who participate to trade in regional market. It concerns with entrepreneur spirit among Minangkabau societies. It also explores the relationship between entrepreneurship and economic empowerment either locally (West Sumatera area) and nationally. There are several reasons for women traders jumped into the export trade; firstly, they want to continue their family life. Secondly, there is such inequality of ownership of agricultural land area. Thirdly, there are many low education levels found in society. Lastly, Minangkabau ethnics are recognized as very good traders (social culture). The presence of women traders in the regional market is an incubator and the birth of the entrepreneur spirit for the next generation. It also contributes to the economic empowerment of West Sumatra in particular and the national economy in general.